2010
DOI: 10.1007/s00508-010-1395-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary large-cell neuroendocrine carcinoma of the scrotum

Abstract: Neuroendocrine tumors (NETs) mostly develop from the neural crest cells but a few arise from neuroectoderm. They are common in the lungs and gastrointestinal tract but rare in the genitourinary tract. A 78-year-old man with no family history of malignant or hereditary diseases presented with a 3-month history of a rapidly growing asymptomatic scrotal nodule and swelling in the groin. He had a negative history of sexually transmitted disease and of trauma, fungal infection or chronic irritation in the scrotal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…CAPTEM have been known to be active in the first-line setting for advanced pancreatic neuroendocrine neoplasms. 3 meta-analysis to study safety and efficacy of treating patients with advanced NETs with CAPTEM showed the combination to be both effective and relatively safe in a variety of different malignancies. 5,6 In addition, the high objective response rates, achieved with CAPTEM makes it natural choice for patients who are heavily pretreated and "chemo resistant" until this regimen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CAPTEM have been known to be active in the first-line setting for advanced pancreatic neuroendocrine neoplasms. 3 meta-analysis to study safety and efficacy of treating patients with advanced NETs with CAPTEM showed the combination to be both effective and relatively safe in a variety of different malignancies. 5,6 In addition, the high objective response rates, achieved with CAPTEM makes it natural choice for patients who are heavily pretreated and "chemo resistant" until this regimen.…”
Section: Discussionmentioning
confidence: 99%
“…1 They are more commonly found in the lungs and gastrointestinal tract, but are rare in the genitourinary tract. 2,3 They are more common in women. 3 Most male genital tract NETs are prostatic small cell carcinomas or testicular carcinoids.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The published reports usually come from small, single-institution series [2, 3, 4, 5]. Among the primary scrotal cancers, the most common histologic type is squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%